To Assess the Knowledge on Gastro Intestinal Bleeding Among Nursing Students and Faculty in Pondicherry Institute of Medical Sciences - R, Rajalakshmi.; S, Malarvi Zhi.; K, Mony (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2022)
Acute Gastrointestinal Bleeding is a very common medical emergency with a hospital mortality of approximately 10 percent. Higher mortality rate is associated with re-bleeding. Rockall scoring system identifies patients at higher risk of rebleed and mortality. The present study was aimed to assess the Knowledge on gastrointestinal bleeding among student nurses and nursing faculty in college of nursing at Pondicherry Institute of Medical Science’’. 88 Participants were selected by simple random sampling. Among 88 participants level of knowledge in pre-test 3 % have mild knowledge, 24% had moderate knowledge and 73% had adequate knowledge. level of knowledge in post-test 2.3 % have mild knowledge, 5.4% had moderate knowledge and 92.3% had adequate knowledge. Level of knowledge is increase from pre-test to post-test. It shows that the lecture is effective. difference between the pre test score and post test score is 1.11 which shows that it is statistically significant at p<0.001. The current study recommended that they have to be educated about the gastrointestinal bleeding.